Adaptive architecture; historical buildings adapted to sea level rise - Klevell, Marika (My University, 2024)
Rising sea levels threaten many areas worldwide and in combination with extreme weather events such as storms and heavy rain, the challenge of keeping cities and areas above water is growing. The investigation takes place in Klippan in Gothenburg harbor which is vulnerable to flooding caused by rising sea levels. The city has a strong connection to water as it is situated on the west coast and further inland along the river Göta älv. Klippan played a significant role as a port location for Gothenburg harbor during the 17th century. To preserve the history and the characteristics of Klippan it has since then been declared as a cultural reserve. The reserve has a mix of buildings still standing from companies such as Ostindiska kompaniet and Carnegie’s sockerbruk. The region located in Klippan, which runs along the river, has an elevation that varies from 1 to 2 meters. As a result, the shoreline is prone to flooding. It is estimated that by the year 2100, large parts of the area are likely to be flooded during storms and high waters. The investigation was centered on two historically valuable buildings in Klippan, which are at risk of flooding by 2100. With similar situations as a starting point, Sjömagasinet and Klippans Konstcafé were retrofitted with two different strategies depending on their conditions to adapt them to rising sea levels. Depending on which strategy is applied, the program of the building may be affected. It is explored through the two buildings, resulting in a new program for Klippans Konstcafé while the program for Sjömagasinet is preserved. The thesis questions how the choice of retrofitting strategy affects an existing building’s program. There’s a strong reason to implement retrofitting strategies from a preservational point of view in Klippan. The proposal showcases an example of how one can preserve the historical and architectural qualities of structures in a flood-prone area, while also ensuring that the buildings can function during high waters caused by rising sea levels and increased extreme weather conditions.
Keywords: Klippan, sea level rise, retrofitting